Unfolding the secrets of Pascal’s Triangle: patterns, applications and mathematical beauty / Siti Zaharah Mohd Ruslan - Mohd Ruslan, Siti Zaharah (Universiti Teknologi MARA, Negeri Sembilan, 2025)
One of mathematics' most fascinating and useful structures is Pascal's Triangle. Although it appears to be straight forward triangle of integers at first glance, it actually has a surprisingly large number of mathematical properties and practical uses. From probability and algebra to computer science and the natural world, Pascal's Triangle patterns can be found in unexpected areas. This article explores the depth, beauty, and practical uses of this remarkable mathematical structure.